2022
DOI: 10.3389/fgene.2021.799681
|View full text |Cite
|
Sign up to set email alerts
|

A Heterochromatic Knob Reducing the Flowering Time in Maize

Abstract: Maize flowering time is an important agronomic trait, which has been associated with variations in the genome size and heterochromatic knobs content. We integrated three steps to show this association. Firstly, we selected inbred lines varying for heterochromatic knob composition at specific sites in the homozygous state. Then, we produced homozygous and heterozygous hybrids for knobs. Second, we measured the genome size and flowering time for all materials. Knob composition did not affect the genome size and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The total repeat content in Ames21814 was much higher than 1860 Mb in B73, due to the contribution of the Knob and CentC repeats in maize (~10.15%) (Fig. 1d and Supplementary Table 4), where previous study showed that Knobs could affect local recombination 22 . The LTR Assembly Index (LAI) score 23 (LAI=33.07) indicated the Ames21814 haplotype could be a useful reference to discover valuable alleles in the wild maize ancestoral genome.…”
Section: Haplotype-resolved Assembly Of Ames21814 Genome Using Trio-b...mentioning
confidence: 75%
“…The total repeat content in Ames21814 was much higher than 1860 Mb in B73, due to the contribution of the Knob and CentC repeats in maize (~10.15%) (Fig. 1d and Supplementary Table 4), where previous study showed that Knobs could affect local recombination 22 . The LTR Assembly Index (LAI) score 23 (LAI=33.07) indicated the Ames21814 haplotype could be a useful reference to discover valuable alleles in the wild maize ancestoral genome.…”
Section: Haplotype-resolved Assembly Of Ames21814 Genome Using Trio-b...mentioning
confidence: 75%